2018
DOI: 10.1002/dc.24139
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of cytological specimen adequacy assessment by different rapid staining techniques for rapid on‐site evaluation in fine needle aspiration cytology and their cost‐effectiveness

Abstract: Objective Rapid on‐site evaluation (ROSE) is a technique beneficial in determining the adequacy of the samples, thereby increasing the diagnostic yield, useful in triage of specimens for ancillary studies and can also help determine a preliminary diagnosis in emergency cases. The different rapid stains for on‐site evaluation described in the literature are diff quik, toluidine blue (TB), brilliant cresyl blue (BCB), ultra‐fast Pap stains, and rapid hematoxylin and eosin (H&E). This study was undertaken as ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
(24 reference statements)
0
6
1
Order By: Relevance
“…The touch preparation slides are then either air-dried and stained with Diff-Quik stain per standard protocols or ethanol-fixed and stained with rapid Pap stain per standard protocols. From our study, there was a higher proportion of rapid Pap-stained slides that were interpreted as non-diagnostic due to hypocellularity as compared to Diff-Quik stained slides, possibly related to the differences in stain preparation, although these results are in contrast with other studies in the literature in which rapid Pap stain was found to have superior yield and accuracy 21,22. At our facility, more cytopathologists prefer to utilize the rapid Pap stain.…”
contrasting
confidence: 73%
“…The touch preparation slides are then either air-dried and stained with Diff-Quik stain per standard protocols or ethanol-fixed and stained with rapid Pap stain per standard protocols. From our study, there was a higher proportion of rapid Pap-stained slides that were interpreted as non-diagnostic due to hypocellularity as compared to Diff-Quik stained slides, possibly related to the differences in stain preparation, although these results are in contrast with other studies in the literature in which rapid Pap stain was found to have superior yield and accuracy 21,22. At our facility, more cytopathologists prefer to utilize the rapid Pap stain.…”
contrasting
confidence: 73%
“…Finally, depending on each laboratory's practice, cytopathologists may prefer alcohol-fixed over air-dried slides. Conversely, the time required is longer than the nominally 5 s (without air-drying and fixation, respectively) reported for brilliant cresyl blue or a specific modification of toluidine blue [3], but in contrast to these our protocol does not compromise on staining quality. This is particularly important when -as in the case of our interdisciplinary thyroid FNA unit -not only specimen adequacy is assessed but also provisional diagnoses are communicated or triage for ancillary testing is required.…”
Section: Discussionmentioning
confidence: 81%
“…Common stains include modifications of the Romanowsky-type stains (Diff-Quik etc. ), Papanicolaou or Hematoxylin-Eosin stains, and brilliant cresyl blue [3]. From a practical point of view, the number and type of staining components and solvents required are additional factors influencing the feasibility of a particular protocol, given that all must be transported from the cytopathology laboratory to the site of assessment and back.…”
Section: Introductionmentioning
confidence: 99%
“…ROSE specimens used in this study had three features. First, ROSE specimens at our institution were created by rapid hematoxylin and eosin staining, which has been reported to provide almost the same findings as rapid Papanicolaou staining [23] and has been reported not to affect DNA analysis [24]. Second, ROSE specimens at our institution were evaluated by a cytotechnologist to assess sample adequacy.…”
Section: Discussionmentioning
confidence: 99%